GLOBAL VA MILLIY IQTISODIYOTNI RIVOJLANTIRISH MILLAT UMIDI UNIVERSITY (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In the article, the need for more rational and efficient use of limited resources is the main issue of the economy and the main issue is the guarantee of the stabilization process of the economy.